TRANSIENT MANTLE CONVECTION ON VENUS: THE PARADOXICAL COEXISTENCE OF HIGHLANDS AND CORONAE IN THE BAT REGION - Robin C.M.I.; Jellinek A.M.; Thayalan V.; Lenardic A. (My University, 2007)
The coexistence of Venusian highlands, attributed to long-lived axisymmetric mantle plumes, and uncompensated coronae, attributed to transient discrete mantle 'thermals', is difficult to reconcile with models of mantle convection under thermally steady-state conditions. However, cratering and geological studies indicate a uniformly young surface age (~ 700 Myr) as well as a comparable timescale for resurfacing (~ 100 to 400 Myr), possibly consistent with a recent lithospheric overturn and a transient mantle thermal regime. We use laboratory experiments on free and forced thermal convection at high Rayleigh number (Ra ~ 107) in a variable viscosity fluid to investigate the steady-state and transient thermal regimes preceding and following such an overturn. From analyses of shadowgraph images and time series of global and local variations in temperature, basal heat flux and viscosity, we establish steady-state stagnant- and active-lid states and characterize two intermediate transient regimes. Flow in steady-state stagnant lid is in the form of intermittent thermals, consistent with published work. During the transition to active-lid convection the stagnant lid is stirred into the interior using a conveyor belt. Spreading of this cold fluid along the hot boundary leads to a transition to a "mixed mode" of flow from the hot boundary: approximately isoviscous thermals rise from the thermal boundary layer ahead of the advancing cold front and low viscosity plumes rise from behind the front, as a result of an enhanced temperature contrast. The longevity of this regime and the timescale for the transient depends on the rate of overturn (Pe) and the aspect ratio of the system (A). The magnitude of local temperature, viscosity and heat flux variations increases with Pe and can exceed steady-state values for active-lid convection. Additional numerical simulations show that the mixed mode regime will occur in the presence of internal heating, and for no- and free-slip boundaries. In contrast, the transition from active-lid to stagnant-lid convection is marked by a change from a flow composed of plumes and large-scale overturning motions to a regime dominated by rising and sinking thermals on a timescale of thermal diffusion. Applied to Venus, our results support a hypothesis that the contemporaneous coexistence of the Atla and Beta highlands regions with interspersed uncompensated coronae is consistent with a transient thermal regime following a lithospheric overturn. It is also expected that such coronae formed > 250 Myr after the uplift of the highlands. Implications of the thermal origin of coronae for Venusian mantle structure are also explored. © 2007 Elsevier B.V. All rights reserved.
Keywords: CORONAE; HIGHLANDS; MANTLE THERMALS AND MANTLE PLUMES; TRANSIENT MANTLE CONVECTION; VENUS